UJI EFEK ANALGESIK EKSTRAK DAUN SIRIH HIJAU BANYUWANGI (Piper betle L.) PADA MENCIT PUTIH JANTAN (Mus musculus) - Lestari, Ima Fitria; Syafirah, Junieta Fara; Deviani, Dita Amanda (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
The content of flavonoid compounds in betel leaf is used as a protection as analgesic. The purpose of this study was to test the analgesic effects of Banyuwangi green betel leaf extract (Piper betle L.) on male white mice (Mus musculus). The doses of green betel leaf ethanol extract that were used were 4.696 mg, 9.392 mg and 18.784 mg and the positive control were mefenamic acid. The test animals used in this study were white male mice (Mus musculus) that were adapted for about 3 days in experimental environmental conditions. Based on the results of the study, the analgesic effect test of green betel leaf extract (Piper betle L.) can provide analgesic effectiveness on mice (Mus musculus). Ethanol extracts of green betel leaf (Piper betle L.) at doses of 4.696 mg/kgBW were able to provide a good analgesic effect with good responses to white male mice (Mus musculus). The percentage of analgesic power that was close to the percentage of analgesic power of the gold standard which is 69.23%.